El género y la interseccionalidad en las cineastas ecuatorianas Viviana Cordero y Tania Hermida (De La Escena Contemporánea) - Roberts-Camps, Traci (2021)
The purpose of this essay is to analyze the dynamics of power and oppression in Viviana Cordero’s No robarás... (a menos que sea necesario) (2013) and Tania Hermida’s En el nombre de la hija (2011) using the theory of intersectionality. These pages examine how these directors explore themes of gender, ethnicity, social class and age. The perspective of intersectionality - understood as the recognition of the importance of different aspects of identity and how they intertwine and affect each other - is central to this analysis. Likewise, the systems of power that marginalize Cordero and Hermida’s protagonists are highlighted.